Literature and the other arts: postmodern poetry in English - Oliveira, Solange Ribeiro de (Aletria: Revista de Estudos de Literatura, 2009)
Resumo: Partindo da tendência pós-moderna para a eliminação de fronteiras entre as artes e mídias, o artigo analisa as relações intermidiáticas frequentes na poesia pós-moderna de expressão inglesa.Palavras-chave: intermidialidade; literatura e as outras artes; poesia pós-moderna de expressão inglesa.Abstract: Starting from the postmodern tendency towards the erasing of frontiers between the arts and the media, the essay analyses the frequent intermedial relations in postmodern poetry in English.Keywords: intermediality; literature and the other arts; postmodern poetry in English.